Respuesta :

[tex]\dfrac{4}{9}(x+3)=g\ \ \ \ |multiply\ both\ sides\ by\ 9\\\\4(x+3)=9g\ \ \ \ |use\ distributive\ property:a(b+c)=ab+ac\\\\4x+12=9g\ \ \ \ |subtract\ 12\ from\ both\ sides\\\\4x=9g-12\ \ \ \ |divide\ both\ sides\ by\ 4\\\\\boxed{x=\frac{9}{4}g-3}[/tex]
[tex] \frac{4}{9(x+3)} = g [/tex] 

[tex] \frac{4(x+3)}{9} =g[/tex] 

 [tex]4(x+3)=g*9[/tex]       [tex]||Multiply- both -sides -by-\ \textgreater \ 9||[/tex]  

[tex]4(x+3)=9g[/tex]         [tex]||Regroup -terms||[/tex] 

[tex]x+3= \frac{9g}{4} [/tex]    [tex]||Divide- both -sides- by-\ \textgreater \ 4||[/tex] 

[tex]x= \frac{9g}{4} -3[/tex]
 


Otras preguntas